Diagnosing and treating esophageal obstruction in camels (Camelus dromedarius) - Madeh Sadan; Sabry El-Khodery; Saleh Almatroodi; Fahd Alsobayil; El-Sayed El-Shafaey (Veterinary World, 2023)
Background and Aim: Esophageal obstruction is a common occurrence and a serious condition in camels. This study aimed to assess the effects of mineral deficiency on esophageal obstruction rates in dromedary camels and describe their clinical presentation and treatment outcomes.